Impact of Arabica Coffee Production on Social Welfare: A Comprehensive Analysis - Annisa Ilmi Faried; Uswatun Hasanah; Rahmad Sembiring (Yayasan Multidimensi Kreatif, 2023)
The flavor and quantity of Arabica coffee are considered to be superior to those of Robusta coffee, and Arabica coffee also contains a lower amount of caffeine. Arabica coffee production and community welfare are known as factors Y in this study. Labor, consumption, land area, and distribution are referred to as variables X. This study was conducted using the Path Analysis method in Sinaman II Village to Pamatang Sidamanik District, Simalungun Regency. Using the SPSS program version 24.0 for Windows, the data that was collected from the distribution of questionnaires was processed. Through the use of arabica coffee output as an intervening variable in Sinaman II Village, the objective of this study is to investigate the impact that these important or positive aspects have on the well-being of farming communities. The findings, which were based on path analysis, demonstrated that the wellbeing of the community is influenced collectively by the independent variables of labor, consumption, land area, and distribution. Additionally, the production of Arabica coffee is able to accommodate any and all circumstances.